From Season to Season. Sports as American Religion, edited by J.L. Price. Macon, GA: Mercer UP, 2001. 9780865546943 and The Great God Baseball. Religion in Modern Baseball Fiction, by A.E. Hye. Macon, GA: Mercer UP, 2004. 9780865549319 - Grimshaw, Michael (Implicit Religion, 2009)
From Season to Season. Sports as American Religion, edited by Joseph L. Price. Macon, GA: Mercer University Press, 2001. ISBN-13: 9780865546943, 240pp., hb 45.00. The Great God Baseball. Religion in Modern Baseball Fiction, by Allen E. Hye. Macon, GA: Mercer University Press, 2004. ISBN-13: 9780865549319, 192 pp., HB 40.00.